Selenite elimination via zero-valent iron modified biochar synthesized from tobacco straw and copper slag: Mechanisms and agro-industrial practicality - Luo, Qiong; Chen, Dingxiang; Cui, Ting; Duan, Ran; Wen, Yi; Deng, Fang; Li, Lifang; Wang, Huabin; Zhang, Yong; Xu, Rui (Frontiers in Bioengineering and Biotechnology, 2022)
Biochar performance improvement with more cost-effective way is essential for its large-scale practical application. In this work, the agro-industrial byproducts, copper slag and tobacco straw were employed for the preparation of modified biochar (CSBC). The irons species from copper slag was successfully loaded onto the biomass substrate as Fe0, Fe2O3, Fe3O4, and etc. The obtained CSBC exhibited satisfied capacity on Se(IV) immobilization 190.53 mg/g, with the surface interactions of determined by monolayer and mainly chemisorption. Further, the removal mechanisms involved chemical reduction, electrostatic attraction, co-precipitation, and formation of complexations. Interestingly, the existence of Cu2Se structure after adsorption indicated the involvement of Cu species within Se(IV) elimination. Moreover, the industrial agricultural practicality of CSBC was evaluated by regeneration tests, economic assessment, and pot experiments. All these results demonstrated that iron species modified biochar prepared from two agro-industrial by-products were promising and feasible for the selenite removal from wastewater.